Acute lower respiratory tract infections and associated factors among under-five children visiting Wolaita Sodo University Teaching and Referral Hospital, Wolaita Sodo, Ethiopia - Birhanu Wondimeneh Demissie; Esayas Aydiko Amele; Yibeltal Asmamaw Yitayew; Zemen Mengesha Yalew (BMC, 2021)
Abstract Background Lower respiratory infections are a leading cause of morbidity and mortality worldwide, particularly in children younger than 5 years. Even if the burden of lower respiratory infections in children under 5 years old had decreased dramatically in the last 10 years, it is still the main cause of morbidity and mortality in children under-5 years old in developing countries, so the aim of this study was to assess the magnitude of lower respiratory tract infections and associated factors among under-five children visiting Wolaita Sodo University Teaching and Referral Hospital. Method A cross-sectional study was conducted from 1st to 30th April 2019, among under-five child/mother or caretaker pairs visiting Wolaita Sodo University Teaching and Referral Hospital. Child/mother or caretaker pairs who visits outpatient department for curative care service or follow up were recruited for the study. Data were collected using a semi-structured pre-tested interviewer-guided questionnaire. Epi-info (version 7.1.2.0) was used for data entry, and Statistical Package for Social Sciences version 20 was used for analysis. Bivariate and multivariate logistic regression, crude and adjusted odds ratios with their 95 % confidence intervals was computed. Finally, a p-value ≤ 0.05 was used to identify variables that had a significant association with acute lower respiratory infection. Result A total of 414 child/mother or caretaker pairs were recruited for the study. The magnitude of acute lower respiratory infections among under-five children was 40.3 % (95 % CI: 35.7- 44.9 %). Unvaccinated children (AOR: 2, 95 % CI, (1.27-3.16)), non-exclusive/replacement feeding (AOR: 1.85, 95 % CI, (1.18-2.91)), households mainly used unclean fuel for cooking (AOR: 2.12, 95 % CI, (1.07-4.19)), absence of separate kitchen (AOR: 1.7, 95 % CI, (1.09-2.65)), and absence of window in the kitchen room (AOR: 1.69, 95 % CI, (1.07-2.68)) showed significant association with acute lower respiratory infection. Conclusions The magnitude of acute lower respiratory tract infections among under-five children visiting outpatient department was 40.3 %. Unvaccinated children, non-exclusive/replacement feeding, using unclean fuel for cooking, absence of a separate kitchen, and absence of window in the kitchen showed significant association with acute lower respiratory infection. Therefore, special attention should be given to the environmental sanitation and family health components of health extension packages.